Prevalence and factors associated with augmented renal clearance after surgery - Mustapha, Muhammad Ikhwan; Othman, Ahmad Faidzal; Mat Nor, Mohd Basri; Md Ralib, Azrina; Ab Rahman, Jamalludin; Elagili, Faisal (2022)
Introduction Augmented Renal Clearance (ARC) has been described mainly in critically ill patients which may place patients at risk of therapeutic failure. We investigated the prevalence of ARC following surgery, determine the risk factors and the outcome.